The Representation of Students' Mathematical Concepts in Algebraic Problems Solving Based on Mathematical Ability - Mustangin Mustangin; St Suwarsono; Agung Lukito (International Journal of Trends in Mathematics Education Research, 2020)
This study aims to describe the representation of students' mathematical concepts in solving algebraic problems based on mathematical ability. This study is exploratory descriptive qualitative with four junior high school students as subjects. Data were collected using a task-based interview and analyzed using qualitative data analysis techniques through data reduction, data presentation, and drawing conclusions. The mathematical ability is categorized into high and low.  The results show that differences in mathematical ability has no real effect on the representation of mathematical concepts of students in algebraic problem solving. Proved by all subjects (low and high mathematical abilities) are able to solve algebraic problems using verbal, symbolic, imagistic, and notational formal representations. However, there is a difference on the model of mathematical representation used. Students with high ability prefer to use conceptual representations using conventional standard notations, while those with low mathematical ability tend to use pictorial representations using non-standard illustrations.